Erosion of the property tax base : trends, causes, and consequences - Augustine, Nancy Y. (Lincoln Institute of Land Policy, 2009)
Increased reliance on residential property to generate tax revenue and soaring property values in many parts of the country have placed pressure on local officials to respond to concerns about higher property taxes. The result has been erosion of the property tax base through a variety of policies designed to relieve residential property tax burdens through exemptions or abatements. The chapters in this book provide analyses of recent property tax trends; examine several responses to the increasing importance of residential property; estimate the extent of property tax base erosion and its effects; and consider other related topics. The erosion of the property tax base raises serious concerns about the future health of our federal system of government and the continued ability of local governments to protect what de Tocqueville called America's passion for popular sovereignty. - Publisher.